2012
DOI: 10.5751/es-04610-170133
|View full text |Cite
|
Sign up to set email alerts
|

A Wall out of Place: a Hydrological and Sociocultural Analysis of Physical Changes to the Lakeshore of Como, Italy

Abstract: A wall out of place: a hydrological and sociocultural analysis of physical changes to the lakeshore of Como, Italy. ABSTRACT. The construction of a flood protection structure that obscured views of the lake in Como, northern Italy, led to unprecedented public protest in 2009-2010 and to the eventual dismantlement of the structure. This provided a focus to investigate the delicate interplay of technical and cultural matters in environmental policy-in this case, catchment management and flood prevention. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The model provided a suitable general workflow for urban planning and furnished guidance for choosing proper operational techniques. The workflow also highlighted the need for a robust organization and control over construction works, as well as good communication with the public and proper investigation of the delicate interplay of technical and cultural matters in environmental policy (see for instance the discussion in Laborde et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The model provided a suitable general workflow for urban planning and furnished guidance for choosing proper operational techniques. The workflow also highlighted the need for a robust organization and control over construction works, as well as good communication with the public and proper investigation of the delicate interplay of technical and cultural matters in environmental policy (see for instance the discussion in Laborde et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A further issue, relevant to the above, takes us to cross‐disciplinary research in water use which has been shown to be highly productive, for example, anthropology working collaboratively with human geography, ecology, environmental studies, and hydrology (Jackson and Head 2022; Laborde et al 2012). Cross‐disciplinary research presents no reason why or obstruction to Australian Aboriginal people communicating directly with government authorities, physical scientists, and bureaucratic planners about water futures, especially in the 21st century.…”
Section: Stories About Watermentioning
confidence: 99%